BRINGIN TRAIN STATION HISTORICAL LEARNING VIDEO TO IMMERSE SENIOR HIGH SCHOOL STUDENT HISTORICAL AWARENESS - pahlawan, ananda ahmad; Sunardi, Sunardi; Wuryani, Emy (Jurnal Penelitian Pendidikan Sejarah UHO, 2021)
Historical awareness is an important component in shaping and preserving the nation's culture. Today, many students begin to ignore the importance of learning history. President Soekarno said that "Jasmerah" should never forget history. Therefore, to instill historical awareness for high school students, relevant learning media were made, by taking the colonial building of the Bringin Railway Station as a learning resource. The history of the Bringin Train Station is made into a creative and innovative learning video. This research method, using a 10-stage development model from Dick & Carey and statistical analysis techniques paired sample T-test which was carried out with the help of SPSS software. The results of the research conducted are proof that there is a significant increase in the value of the experimental class and a slight increase in the control class. So, it can be concluded that the instructional video media of the History of the Bringin Railway Station is proven to be effective in instilling historical awareness in students.